DETERMINANTS OF FINANCIAL SATISFACTION IN GOPAY USERS WITH GENDER AS A MODERATOR (Case Study of University Students in the City of Pekanbaru) - Sari, Desi Novita; Nesneri, Yessi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Financial satisfaction is a component of well-being that includes both subjective and objective factors related to one's financial resources to experience happiness. This study aims to find out financial knowledge, financial skills, financial attitudes, and financial behavior with gender as a moderator. The number of students in Pekanbaru is 129,851, which is used as a quantitative population analysis. The sampling method uses nonprobability sampling with an Accidental Sampling approach. The sample for this study consisted of 275 respondents. The results of this study show that financial knowledge, financial skills, financial attitudes, and financial behavior have a positive and significant influence on financial satisfaction. The influence of financial knowledge on financial satisfaction with gender as a moderator has a positive impact on this relationship. Meanwhile, the influence of financial ability, financial attitudes, and financial behavior on financial satisfaction with gender as a moderator did not have a significant positive impact on this relationship.